Teachers’ Problems and Solutions in Implementing Curriculum 2013 - Apsari, Yanuarti (Acuity: Journal of English Language Pedagogy, Literature and Culture, 2018)
Curriculum 2013 as an effort to reform educational system. However, the Curriculum demands teacher and school to be skilled and trained and because of this, in implementing School Based Curriculum teachers deal with some problems. Thus, this study aims to find out the problems faced by the English teacher in implementing Curriculum 2013 and their solution to overcome those problems. With regard to the purpose of the research, a qualitative approach was employed. The data were obtained through observation, questionnaires and documents. The data were transcribed, categorized, and interpreted to answer the research questions. The respondents of this study were three English teachers of three high school in Batujajar. The result of the study showed that dealing with the the implementation of Curriculum 2013 the teachers had the problem related to three aspects namely: problems related to teaching and learning process, problems related to creating lesson plan, and problems related with teaching material. It was also revealed that the respondents do some efforts to overcome those problems such as maximizing the provided facilities, cooperating with others teachers, getting involved in workshop or MGMP,searching the example of lesson plan from internet, reading the various sources, copying and using lesson plan from the other schools, download E book, asking for friend to send E book through email and using the previous book. Â  Key Words: Curriculum 2013, Problem and Solution